2010
DOI: 10.1111/j.1464-410x.2010.09804.x
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of tumour‐associated macrophages in prostate biopsy specimens is predictive of disease progression after hormonal therapy for prostate cancer

Abstract: Study Type – Prognostic (case series) Level of Evidence 4 What’s known on the subject? and What does the study add? In general, tumour‐associated macrophage (TAM) is important for tumour progression including prostate cancer. In this paper, we clarified the usefulness of TAM in prostate biopsy specimens for predicting prognosis after hormonal therapy. OBJECTIVE • To evaluate tumour‐associated macrophage (TAM) infiltration in prostate biopsy specimens as a possible prognostic factor for prostate cancer (PCa) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
149
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(165 citation statements)
references
References 22 publications
8
149
0
1
Order By: Relevance
“…Regarding the association between the prognostic parameters and biochemical progression in our study, we found a significant association between the conventional parameters including the initial PSa level, gleason score ≥7, and tumor tNM stage with biochemical progression as previously reported by other investigators (37)(38)(39). In addition, early biochemical recurrence was more prevalent in cases with high twist-1, aberrant E-cadherin, and high EZH2 expression.…”
supporting
confidence: 88%
“…Regarding the association between the prognostic parameters and biochemical progression in our study, we found a significant association between the conventional parameters including the initial PSa level, gleason score ≥7, and tumor tNM stage with biochemical progression as previously reported by other investigators (37)(38)(39). In addition, early biochemical recurrence was more prevalent in cases with high twist-1, aberrant E-cadherin, and high EZH2 expression.…”
supporting
confidence: 88%
“…Lymphocytes and macrophages present in the prostate are most often associated with this chronic inflammation, and less frequently plasma cells, eosinophils, and neutrophils (63,64). The presence of tumor-associated macrophages have been reported as potential biomarkers of poor prognosis in prostate cancers (65,66), and we have evidence that these macrophages can be detected by flow cytometry of the low speed cell pellets of EPS urine samples in a subset of prostate cancer patients (data not shown). A better understanding of the role of the many detectable biomarkers of immune system activity, like the members of the complement pathway overexpressed in nonorgan-confined EPS samples, is critical for improving diagnostic targeting of aggressive prostate cancers.…”
Section: Discussionmentioning
confidence: 63%
“…This same group later reported that lower numbers of prostate-infiltrating class A macrophage scavenger receptor (SR-A)-expressing cells (dendritic cells and macrophages) were similarly associated with higher clinical stage and positive lymph nodes and predictive of shorter time to PSA progression (Yang et al 2004). Although the intriguing positive association of macrophage numbers with Gleason score has held up in multiple additional studies, TAM quantification as an independent prognostic factor Hao et al (2012) for time to PSA progression has varied (Lissbrant et al 2000;Wang et al 2005;Nonomura et al 2011). In a study on disease progression after hormone therapy for prostate cancer, TAM densities as assayed by IHC for CD68 on patient's prostate biopsy specimens prior to treatment were found to be positively correlated with Gleason score and clinical stage (Nonomura et al 2011).…”
Section: Macrophages In Prostate Cancermentioning
confidence: 99%
“…Although the intriguing positive association of macrophage numbers with Gleason score has held up in multiple additional studies, TAM quantification as an independent prognostic factor Hao et al (2012) for time to PSA progression has varied (Lissbrant et al 2000;Wang et al 2005;Nonomura et al 2011). In a study on disease progression after hormone therapy for prostate cancer, TAM densities as assayed by IHC for CD68 on patient's prostate biopsy specimens prior to treatment were found to be positively correlated with Gleason score and clinical stage (Nonomura et al 2011). Furthermore, in contrast to the studies by Shimura et al (2000) and Yang et al (2004), Nonomura et al reported that increased numbers of TAMs were significantly associated with PSA progression and serve as a prognostic indicator for decreased time to progression-free survival (Nonomura et al 2011).…”
Section: Macrophages In Prostate Cancermentioning
confidence: 99%